Combat Sports Medicine - Wallace, W. Angus.; Wroble, Randall R.; Maffulli, Nicola.; Kordi, Ramin. (Springer London, 2009)
A significant body of scientific knowledge has been published in sports medicine in the past few decades, but there is huge demand for practical references that address different types of sport. This demand is highest in combat sports which are both highly physical and mentally demanding, and cause challenging issues such as risk of blood borne infections, weight reduction, head injuries, and stress management. Combat Sports Medicine has two parts, the first dealing with common topics in many combat sports: nutrition and psychology; ethical and social issues, including doping; injuries and infections; and combat sports in specific groups. The second part of the book covers aspects of sports science and injuries in selected popular combat sports are discussed. An international team of contributors have developed this book to meet the needs of practitioners who work with combat sports athletes. Based on the best available research evidence, this represents a key reference for neurologists, psychologists, orthopedic surgeons and sports injury specialists involved in the management of patients who practice contact sports.